A Design Method for Viscous Dampers Connecting Adjacent Structures - Tubaldi, Enrico; Gioiella, Laura; Scozzese, Fabrizio; Ragni, Laura; Dall'Asta, Andrea (Frontiers in Built Environment, 2020)
This paper investigates the seismic design of fluid viscous dampers connecting adjacent structural systems. A simplified dampers design strategy is proposed, which relies on a linearized reduced order model of the coupled system. A stochastic linearization technique is adopted with the aim of extending the design method to nonlinear viscous dampers. The effectiveness of the design method and of the coupling strategy are assessed via numerical analysis of two adjacent buildings with shear-type behaviour connected by linear or nonlinear viscous dampers and subjected to Gaussian stochastic base acceleration. Different dampers locations are analysed. The accuracy of the reduced order model is assessed, by comparing the relevant response statistics to those provided by a refined multi degree of freedoms model. Finally, a parametric study is performed to assess the effectiveness of dissipative connection for different values of seismic intensity and dampers parameters (i.e., viscous coefficients and velocity exponents).